PENINGKATAN PENGETAHUAN IMPLEMENTASI SENSOR-SENSOR PENDUKUNG TEKNOLOGI INTERNET OF THINGS BAGI GURU SMK WALISONGO SEMARANG - Febrian Wahyu Christanto; April Firman Daru; Vensy Vydia (Unika Santu Paulus Ruteng, 2022)
Internet of Things is a phenomenon of information technology not only playing a role in the economic field, but also in the field of education. Today every teacher, especially at Vocational High Schools (SMK) is required to teach information technology, one of which is the Internet of Things. As such, it meets the needs of the industrial world which requiring skills and competitiveness in the technology from the vocational school graduates. This encourages teachers to always update knowledge about the development of information technology. However, not all information technology can be taught optimally, especially sensors material and its implementation on the Internet of Things. This occurs as the Internet of Things is a fairly new technology. In addition, the time for teachers to learn the latest technology is limited due to unsupported facilities and administrative tasks that need to be completed immediately. This has an impact on the minimum level of teacher mastery for sensors that support Internet of Things technology including teachers at the SMK Walisongo Semarang. Through the Community Service (PkM) program at the Universitas Semarang which was held on Tuesday, November 2, 2021, the PkM team expected an increasing knowledge of the implementation of sensors supporting Internet of Things technology for teachers at SMK Walisongo Semarang. There are 4 types of sensors used in this PkM program, namely proximity sensors, humidity sensors, temperature sensors, and light sensors which will be presented using the practical method. The PkM that has been carried out, it is found that the results of this service is that the knowledge of teachers on Internet of Things sensors has increased up to 75%.. It is hoped that this program will be a will increase teacher knowledge at the SMK Walisongo Semarang and can help them create vocational graduates who have the skills and competitiveness in the world of technology.